Leadership Coaching and Transformation in the South African Mining Sector - Sibindi, Mandla; Ndlovu, Elona N (Journal of Leadership in Organizations, 2024)
Introduction/Main Objectives: This study investigates the role of leadership coaching in addressing transformation challenges in South Africa's mining sector. Given the slow pace of transformation, it is critical to understand how coaching can help. Background Problems: The study focuses on leadership coaching and its impact on Historically Disadvantaged South Africans (HDSA) being developed for transformation roles. The central research question is how long-term transformation in the mining industry is facilitated by leadership coaching. Novelty: Prior studies on transformation and coaching have generally been broad and not specific to the mining sector, our research fills a critical gap. The study provides a unique perspective by investigating coaching's impact on mining industry transformation. Research Methods: Semi-structured interviews were conducted with mining industry human resources managers, coaches, and coaches. The data was analysed using thematic analysis, ensuring a robust and data-driven approach. Finding/Results: The results of the study revealed that leadership coaching effectively supports the development of HDSA individuals in transformation vacancies. However, it is critical to recognise that coaching is only one component of successful transformation; other factors are also important. Within the mining industry, there are also barriers to transformation and coaching. Conclusion: Leadership coaching emerges as a dynamic force, propelling transformative change in the mining sector. Beyond racial transformation, participants reveal its strategic use for legal compliance, social responsibility, and financial optimisation. A holistic approach, emphasising coaching's multifaceted impact on organisational goals. This study contributes to a nuanced understanding of coaching's transformative role in technical industrial environments.